Sistem Informasi Geografis Pemetaan Sebaran Alumni: Sistem Informasi Geografis Pemetaan Sebaran Alumni Pada STMIK STIKOM Indonesia - Adi Panca Saputra Iskandar; I Kadek Dwi Gandika Supartha (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
Alumni data that has been stored is underutilized where this condition is called "rich of data but poor of information". At this time STIKI Indonesia is less aware of specific alumni distribution information in the world of work because there is no system that can do that. These problems can utilize Geographic Information System (GIS) technology. Human resource management is what supports the vision and mission of alumni ties by forming relationships between alumni so that they can provide information about the workplace and job opportunities between one alumni and other alumni. Thus, each alumni can exchange information in a manner and build a circle that can help alumni who are still not working. Geographic Information System is one of the information systems with mapping visualization that has the ability to present information in graphical form using maps as an interface, so that the distribution of alumni can be known specifically (Handoko 2012). Testing using the black box testing method in the Geographical Information System for Alumni Distribution Mapping shows that all modules in the system are functioning properly and can display information as designed